Antifungal active ingredient from the twigs and leaves of Clausena lansium Lour. Skeels (Rutaceae) - Fu, Xiaoxiang; Xiao, Suling; Cao, Duantao; Yuan, Minxuan; Xiang, Miaolian; Zhou, Qinghong; Huang, Yingjin; Wei, Hongyi; Peng, Wenwen (Frontiers in Chemistry, 2022)
Two novel amides, named clauphenamides A and B, and twelve other known compounds were isolated from the twigs and leaves of Clausena lansium Lour. Skeels (Rutaceae). Their structures were elucidated on the basis of extensive spectroscopic analysis and comparison with data reported in the literature. Clauphenamide A (1) featured in the unit of N-2-(4,8-dimethoxyfuro [2,3-b]quinolin-7-yl)vinyl, and clauphenamide B (2) was a unprecedented N-phenethyl cinnamide dimer. Other known compounds belong to pyrrolidone amides (3 and 4), furacoumarins (7–10), simple coumarins (11–14), lignan (5) and sesquiterpene (6). Compounds 5, 6, 10 and 12 were separated from the genus (Clausena) for the first time, while 13 was isolated in the species (C. lansium) for the first time. The antifungal activities of the isolated compounds were assayed. As a result, at the concentration of 100 μg/ml, compared with the control (chlorothalonil, inhibition rate of 83.67%), compounds 1 and 2 were found to exhibit moderate antifungal activity against B. dothidea with inhibition rates of 68.39% and 52.05%, respectively. Compounds 11–14 also exhibited moderate activity against B. dothidea and F. oxysporum, with inhibition rates greater than 40%. In addition, compared with the control (chlorothalonil, inhibition rate of 69.02%), compounds 11–14 showed strong antifungal activity to P. oryzae, with inhibition rates greater than 55%. Among them, compound 14 has the strongest antifungal activity against P. oryzae, and the inhibition rate (65.44%) is close to that of the control chlorothalonil. Additionally, the structure-activity relationships of the separated compounds are also discussed preliminarily in this paper.